Comorbidities associated with epilepsy and headaches - Thalles P. Ferreira; Ana Carolina Coan; Carlos A. M. Guerreiro (Arquivos de Neuro-Psiquiatria, 2012)
Comorbidities are often associated with chronic neurological diseases, such as headache and epilepsy. OBJECTIVES: To identify comorbidities associated with epilepsy and headaches, and to determine possible drug interactions. METHODS: A standardized questionnaire with information about type of epilepsy/headache, medical history, and medication was administered to 80 adult subjects (40 with epilepsy and 40 with chronic headache). RESULTS: Patients with epilepsy had an average of two comorbidities and those with headache of three. For both groups, hypertension was the most prevalent. On average, patients with epilepsy were taking two antiepileptic medications and those with headache were taking only one prophylactic medication. Regarding concomitant medications, patients with epilepsy were in use, on average, of one drug and patients with headache of two. CONCLUSIONS: Patients with chronic neurological diseases, such as epilepsy and headaches, have a high number of comorbidities and they use many medications. This may contribute to poor adherence and interactions between different medications.